(untitled) (Journal of Parents and Teachers, 2014)
In this article of the magazine Padres y Maestros we propose to use didactic research to work on practical activities that allow students to approach the object of study from an analytical and interpretative perspective. In addition, the author presents a series of concrete examples to work on the matter and its changes.